Análisis de costos de producción en cuyes en la parroquia Urdaneta, cantón Saraguro, provincia de Loja - Sarmiento Zhanay, Daniel Alejandro (2024)
Production cost analysis is fundamental in the management of all types of livestock businesses, as it facilitates the documentation, interpretation, and communication of losses or gains inherent to the production system. The objective of the present research project is to conduct a production cost analysis of guinea pigs in the Urdaneta parish, canton of Saraguro, province of Loja, in order to identify the fixed and variable costs of the production systems, as well as, determine the profitability of production through a cost-benefit analysis, and propose a financial accounting model for the management of guinea pig production systems. A total of 40 production units are examined in the study using a non-probability snowball sampling method. In the daily feeding, producers who provide only forage expend an average of $ 2,52, whereas those offering mixed feed spend an average of $ 10,27. Producers who feed only forage generate an income of $ 50,16, resulting in a profitability of $ 1,19. This suggests that for every dollar invested, they gain $ 0,19 within a 37-day period. In contrast, mixed feed producers generate incomes of $ 503,23, resulting in a profitability of $ 3,01 over a 21-day production period, indicating that the production is quite profitable. In conclusion, it is determined that both productions fed exclusively with forage and productions fed in a mixed manner prove to be profitable for the producers, but they differ in terms of the profits obtained, where mixed feed production achieves superior returns.